Longitudinal analysis of microbiome composition in Ghanaians living with HIV-1 - Runtuwene, Lucky Ronald; Parbie, Prince Kofi; Mizutani, Taketoshi; Ishizaka, Aya; Matsuoka, Saori; Abana, Christopher Zaab-Yen; Kushitor, Dennis; Bonney, Evelyn Yayra; Ofori, Sampson Badu; Kiyono, Hiroshi; Ishikawa, Koichi; Ampofo, William Kwabena; et al. (Frontiers in Microbiology, 2024)
Human immunodeficiency virus (HIV) 1 infection is known to cause gut microbiota dysbiosis. Among the causes is the direct infection of HIV-1 in gut-resident CD4 + T cells, causing a cascade of phenomena resulting in the instability of the gut mucosa. The effect of HIV infection on gut microbiome dysbiosis remains unresolved despite antiretroviral therapy. Here, we show the results of a longitudinal study of microbiome analysis of people living with HIV (PLWH). We contrasted the diversity and composition of the microbiome of patients with HIV at the first and second time points (baseline_case and six months later follow-up_case, respectively) with those of healthy individuals (baseline_control). We found that despite low diversity indices in the follow-up_case, the abundance of some genera was recovered to be similar to baseline_control. Some genera were consistently in high abundance in HIV+ samples. Furthermore, we found that the CD4 + T-cell count and soluble CD14 level were significantly related to high and low diversity indices, respectively. We also found that the abundance of some genera was highly correlated with clinical features, especially with antiretroviral duration. This includes genera known to be correlated with worse HIV-1 progression (Achromobacter and Stenotrophomonas) and a genus associated with gut protection (Akkermansia). The fact that a protector of the gut and genera linked with a worse progression of HIV-1 are both enriched may signify that despite the improvement of clinical features, the gut mucosa remains compromised.